The effect of good school governance on school education quality: The moderating role of BOS fund effectiveness: Pengaruh good school governance terhadap kualitas pendidikan di tingkat sekolah: Peran moderasi efektivitas pengelolaan dana BOS - Suryanthi, I Gusti Ayu Eka; Tungga Atmadja, Anantawikrama; Purnamawati, I Gusti Ayu (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2024)
This research examines the influence of good school governance (GSG) on school education quality by using the effectiveness of managing School Operational Assistance (BOS) funds as a mediator variable. The samples in this research were 283 internal and external stakeholders of State Vocational High School (SMKN) 1 Tabanan, Bali. These samples were obtained using the stratified random sampling method. The data analysis method used is path analysis. Hypothesis testing that has a direct effect uses the t-test from the ordinary least square (OLS) regression coefficient results. This research uses the Sobel test to test the hypothesis of the role of mediation or indirect effect. This research proved that accountability and transparency directly affect the quality of school education, but school committee supervision does not. The influence of school committee supervision on the quality of school education is indirect, namely through the mediating role of the effectiveness of BOS fund management. Apart from that, the effectiveness of BOS fund management can also mediate the indirect influence of accountability and transparency on the quality of school education.